ENHANCING BRAND SALIENCE THROUGH PRODUCT PLACEMENT ON VIRTUAL INFLUENCER’S INSTAGRAM - Wijaya, Santrista; Cokki, Cokki (Graduate Program of Universitas Tarumanagara, 2025)
This study seeks to explore the impact of product placement by virtual influencers on the brand salience of two prominent companies, Gucci and Nike. The research involved the participation of 207 students from Tarumanagara University, employing a convenience sampling technique. Utilizing a pre-test and post-test experimental design without a control group, the study incorporated Instagram content featuring a virtual influencer, Alissa Gladys, created by the researcher. Data were collected through Google Forms distributed during fieldwork and subsequently analyzed using SPSS. The findings of the study reveal a positive influence of virtual influencer product placement on brand salience for both Gucci and Nike. Notably, the effect is characterized as moderate for Gucci and small for Nike. This variance is attributed to the distinct product categories represented by the two brands: Gucci, a luxury fashion brand, and Nike, a ubiquitous sportswear brand integral to everyday life. The study contributes to the understanding of the dynamics between virtual influencers and brand awareness, shedding light on how different product categories may be influenced to varying degrees. The utilization of a controlled experimental design and statistical analysis through SPSS enhances the rigor of the research, providing valuable insights for marketing strategies in the context of virtual influencer product placement.